2016
DOI: 10.1002/jcla.21934
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a New and Rapid Method: Brucella Coombs Gel Test With Other Diagnostic Tests

Abstract: According to results BCGT can be used as a diagnostic test in routine laboratories after more comprehensive studies in control groups and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…In our study, sensitivity of BCGT screening with 1/40 dilution of sera as suggested by the producer was found as 97%, while the specificity was 70.3%. Sensitivity rates of BCGT reported in other studies from Turkey (94%-100%) are similar to ours, while the specificity rate we found is lower than the reported 82%-100% rates (13)(14)(15)(16). İrvem et al (13) reported excellent agreement with AHG TAT and an immunocapture agglutination test.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, sensitivity of BCGT screening with 1/40 dilution of sera as suggested by the producer was found as 97%, while the specificity was 70.3%. Sensitivity rates of BCGT reported in other studies from Turkey (94%-100%) are similar to ours, while the specificity rate we found is lower than the reported 82%-100% rates (13)(14)(15)(16). İrvem et al (13) reported excellent agreement with AHG TAT and an immunocapture agglutination test.…”
Section: Discussionsupporting
confidence: 88%
“…Alternative methods, such as the enzyme-linked immunosorbent assay (ELISA) and AHG gel test, with which more samples in shorter time periods can be tested, are presented against standardization problems of agglutination tests with the possibility of different evaluations by different people in different laboratories, but evaluation of these tests is necessary before substitution (6)(7)(8)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity rates of BCGT compared to the Brucella immuncapture test reported in scientific studies from Turkey are between 94-100%, and the specificity rates are between 82-100% [10,21]. Kalem et al [22] performed a study that compared both ELISA and Coombs Gel tests in a similar fashion as in our study. They reported that BCGT and ELISA tests had high sensitivity (100% and 92.8%, respectively) and specificity (100% and 79.7%, respectively) when compared to the immuncapture test.…”
Section: Discussionsupporting
confidence: 65%
“…Values above cutoff were taken as positive. The sensitivity, specificity, positive predictive value (PPV) and, negative predictive value (NPV) of the test are 92.8, 79.7, 50, and 90%, respectively ( 15 ).…”
Section: Methodsmentioning
confidence: 99%